The Impacts of the Use of Outsourced Labor on the Walfare of Workers in Indonesia - Aini, Shafira Nurulita (Jurnal Pengembangan Ketenagakerjaan, 2024)
The writing of the journal "The Impact of the Use of Outsourced Labor on the Welfare of Workers in Indonesia" aims to find out the impact of the use of outsourced labor in Indonesia, the use of outsourced labor can have an impact both positively and negatively, but many rights and rights of outsourced workers are not fulfilled and it causes worker welfare that is not implemented properly, Therefore, action is needed to protect the welfare of outsourcing workers.